Pengaruh Tingkat Pendidikan dan Jumlah Tanggungan Terhadap Kemiskinan Rumah Tangga - Asur Anuz; Sri Endang Saleh; Melizubaida Mahmud; Usman Moonti; Sudirman Sudirman; Imam Prawiranegara Gani (State University of Gorontalo, 2023)
This research aims to determine the influence of education level and the number of dependents on household poverty ini inomunga Village, Kaidipang Subdistrict, North Bolaang Mongondow Regency. This research uses a quantitative approach with survey methodology. The data used are primary data obtained from distributing questionnaires to Inomunga villagers, Kaidipang Subdistrict, North Bolaang Mongondow Regency. The number of samples in this research in 45 respondents. The data analysis technique uses multiple linear regression. The researh indicates a partial and simultaneous effect of education level and the number of dependents on household poverty. The simultanoes effect of education level and the number of dependents on household poverty is 78,9%. The partial effect of education level on household poverty is 31,7%, and the effect of the number of dependents on household poverty is 47,2%.